Edukasi Dan Penggunaan Alat Handsanitizer Menggunakan Pedal Kaki Pada Jemaah Mesjid Dalam Upaya Mencegah Penyebaran Virus Corona (COVID-19) Kota Tanjungpinang - Indra Martias; Ulfa Hanum (Jurnal Salam Sehat Masyarakat (JSSM), 2021)
The sanitation conditions of the mosque that do not meet the requirements have the potential to become a medium for disease transmission and can cause new problems in the surrounding environment. Like the corona virus/covid-19, it can be transmitted through the interaction of the congregation who come to the mosque. The purpose of community service is to provide education to mosque congregations about the corona virus (Covid -19), about the benefits of using a hand sanitizer using a foot pedal to avoid the spread of the Covid-19 virus. The implementation method is designed through several stages including the preparation stage, activity plan, partner participation and activity relevance. The results of this community service include: the community service team held an educational program for managers/marbouts and mosque congregations about the practice of cleaning hands using a hand sanitizer. The hand sanitizer device using a foot pedal is an appropriate technology where its operation does not use a touch of the hand so as to minimize germ/virus contact among mosque congregations. This activity is carried out focusing on health education, so it is hoped that mosque congregations can transmit information to family members at home, so as to create a better household PHBS order. It is hoped that mosque managers can convey information about health protocols in the era of adapting new habits to all mosque congregations. If a positive case of COVID-19 is found in the congregation of the mosque, they will immediately coordinate with the Puskesmas and the Health Office to immediately trace the positive confirmed case.